Students’ perceptions of storytelling online class at the English Education Department - Asep Amrillah; Nur Fatimah; Muhamad Argi Afriandi (Teaching English as a Foreign Language Journal, 2023)
Due to Covid-19, virtual learning at all education levels has been implemented. Storytelling is one of the courses conducted online. The aim of this study is to find out the students’ perceptions on the importance of storytelling, the tasks in an online class of storytelling, and the advantages of learning outcome of online storytelling. This research is qualitative. The data were collected from a storytelling class in an English Education Department in Yogyakarta. They were obtained from an open-ended question questionnaire and interview with 22 students who have attended in storytelling online class. The results show that the students have positive perceptions on storytelling in language teaching. Two of the tasks supporting the storytelling are students’ video recording for storytelling and creating new stories. In relation to the learning outcome, the students’ views that it is advantageous to enhance speaking skills and it results in the learning product such as a story book. This study can be taken into account to improve quality, policies, and program development in English Education Department.